P74 Endometrial cancer: can the iKnife diagnose endometrial cancer?. (1st November 2019) - Marcus, D; Savage, A; Balog, J; Kudo, H; Abda, J; Dina, R; Takats, Z; Ghaem-Maghami, S
Abstract : Introduction/Background: Endometrial cancer is the most common gynaecological cancer in the western world with 88'000 new cases diagnosed per year in the European Union. Diagnosis of endometrial cancer is confirmed by histological examination of endometrial curetting's or outpatient endometrial biopsies e.g. pipelle; but can take up to two weeks. To-date there is no Point-Of-Care (POC) diagnosis available. The intelligent surgical knife ('iKnife') analyses tissue real-time but has never been used to diagnose endometrial cancer. This study aims to establish whether the iKnife could distinguish between normal and malignant endometrial pipelle biopsy samples based on differences in their lipidomic profiles. Methodology: Research pipelle biopsy samples were obtained for women needing biopsies for clinical reasons (samples concurrently sent to conventional histopathology). A Waters G2-XS Xevo Q-Tof mass spectrometer (MS) was used in this study in conjunction with a modified handheld diathermy (collectively coined the 'iKnife'). The resultant surgical aerosol containing ionic species produced during diathermy was then analysed with this technology; producing spectra that are background subtracted, lock mass corrected and in the phospholipid range. Principal component analysis (PCA) and linear discriminant analysis (LDA) were then performed to find the variance in spectral signatures. A leave one patient out cross validation was used to obtain diagnostic accuracy. Results: 134 pipelle biopsy samples (73 normal and 61 malignant) were obtained. Each tissue sample was processed as described; producing an individual spectrum per burn. The iKnife differentiated between normal and malignant endometrial tissues on the basis of differences in their unique phospholipid spectral signatures. Cross validation revealed a diagnostic accuracy of 80%. Conclusion: This pilot study is the first to use the iKnife as a tool to differentiate between normal and malignant endometrial pipelle samples. These results are encouraging and suggest that the iKnife could be used as an adjunct in clinic to provide a POC diagnosis. Disclosure: Nothing to disclose.